Impact of Adding a Decision Aid to Patient Education in Adults with Asthma: A Randomized Clinical Trial. - Myriam E Gagné; France Légaré; Jocelyne Moisan; Louis-Philippe Boulet (PLoS ONE, 2017)
Not providing adequate patient education interventions to asthma patients remains a major care gap. To help asthma patients and caregivers discuss inhaled controller medication use, our team has previously developed a decision aid (DA). We sought to assess whether adding this DA to education interventions improved knowledge, decisional conflict, and asthma control among adults with asthma.A parallel clinical trial (NCT02516449). We recruited adults with asthma, aged 18 to 65 years, prescribed inhaled controller medication to optimize asthma control. Educators randomly allocated participants either to the education + DA or to the education group. At baseline and two-month follow-up, we measured asthma knowledge (primary outcome) with a validated self-administered questionnaire (score -37 to +37). Secondary outcomes included decisional conflict and asthma control. Blinded assessors collected data. Between the two time points, the within- and between-group changes were estimated by generalized linear mixed models.Fifty-one participants (response rate: 53%; age: 44 ± 13 years; women: n = 32) were randomized either to the education + DA group (n = 26) or to the education group (n = 25), and included in statistical analyses. Between baseline and follow-up, mean [95% CI] knowledge scores increased from 21.5 [19.9-23.2] to 25.1 [23.1-27.0] in the education + DA group (P = 0.0002) and from 24.0 [22.3-25.7] to 26.0 [24.0-28.0] in the education group (P = 0.0298). In both of the groups, decisional conflict and asthma control improved. There were no differences between groups.Education improved knowledge, decisional conflict, and asthma control whether the DA was added or not.